Factors Influencing Taxpayer Compliance In The Implementation Of The Land And Building Tax (PBB-P2) Policy In The Revenue Office Districts Of North Jakarta Administrative City And The Kepulauan Seribu Regency - Bambang Eko Prabowo; Maria R. U. D Tambunan (Eduvest - Journal of Universal Studies, 2024)
This research aims to analyze the factors that influence taxpayer compliance with the implementation of the PBB-P2 policy in the Regional Revenue Subdistrict of North Jakarta Administrative City and Kepulauan Seribu Regency using descriptive qualitative data sourced from secondary data. The research results show that from the dimension of policy accuracy, it shows that the implementation of the PBB-P2 incentive policy from the realization of PBB-P2 revenues in the implementation of the incentive policy, there is a less than optimal contribution from the realization of PBB-P2 revenues in the Administrative City of North Jakarta and Thousand Islands Regency during the period 2021 and 2022 which indicates that the tax incentive policy has less influence in increasing PBB-P2 taxpayer compliance in the North Jakarta Administrative City and Seribu Islands Regency areas. Judging from the dimension of accuracy of implementation, problems were found related to PBB-P2 tax potential which had not been optimized, one of which was on Maju Island, which is on a reclamation island in the North Jakarta area. Implementation of the PBB-P2 policy was influenced by the socialization of taxation and digitalization of services. The wider tax socialization carried out through the implementation of optimal digitalization of services can increase PBB-P2 taxpayer compliance. Judging from the dimension of target accuracy in implementing the PBB-P2 incentive policy through socialization of taxation and digitalization of services together, it can influence the level of compliance of PBB-P2 taxpayers in the Regional Revenue Sub-Agency of North Jakarta Administrative City and Kepuluan Seribu Regency.